EVALUASI EFEKTIVITAS PERATURAN DAERAH NOMOR 22 TAHUN 2014 TENTANG RETRIBUSI PELAYANAN PERSAMPAHAN DAN KEBERSIHAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (Studi di Kota Palangka Raya ) (Journal Ilmu Sosial, Politik dan Pemerintahan, 2018)
This study of the resreach to describe and analyze : (1) Describe and analiyze Effectivenees of Local Regulation Number 22 of 2014 on Retribution Waste and Sanitation Services to Intrease the Original Income. (2) Supporting Factors and Inhibiting Effectivenees of Local Regulation Number 22 of 2014 on Retribution Waste and Sanitation Services to Intrease the Original Income. There are 5 (five) Effectivenees Indicators A Program : Namely the succes of the program, target sucess, satisfaction with the program, input and output levels, the achievement of the overall objectives. In the resreach the resreachers used the method Qualitative descriptive. Data Collection techniques using ways observation, interview, and documentation. Based on Resreach results : (1) Local Regulation Number 22 of 2014 on Retribution Waste and Sanitation Palangka Raya City done pretty well and the ralization of the Distribution of waste and sanitation sectors the government has always achived, however still not maximal between input and output due to lack of facilities and infrastructure and community participation and negligence to pay compulsory retribution. This is analyzed from 5 (five) indicators of the effectivenees a program : lack off facilities and infrastructure garbage transport and lack of cooperation between related agencies in the event on sanctions for violations of regional regulations is an onternal factor resulting in a lack of quality waste and sanitation in the Palangka Raya City. And external factors ie lack of awareness and community participation paying retribution and lack of understanding to the important functions and roles of the community in increasing local revenue from the retribution sector so that this local regulation has not been implemented effectively and efficiently. (2) Supporting Factors : the efforts of the relevant agencies to maximize service to the community by making various efforts evaluation of constraints faced and what should be improved in improving service and community participation.(3) Suggestion: The importance of cooperation with related agencies enforcement of sanctions violation ofobligation of pay retribution as well proper socialization to raise awareness and public participation in paying levies on garbage and sanitation services of course by improving supporting facilities an infrastructure which can be perceived by the Society.